Proceedings of the First International Conference on Gameful Design, Research, and Applications 2013
DOI: 10.1145/2583008.2583019
|View full text |Cite
|
Sign up to set email alerts
|

“I want to be a captain! I want to be a captain!”

Abstract: Gamification is increasingly implemented in citizen science projects as a means of motivating and sustaining participation. In a survey and subsequent interviews we explored the appeal of gamification for participants in the Old Weather project, and its impact upon data quality. We found that the same competitive mechanisms which some volunteers found rewarding and motivating were either ignored by other participants, or contributed to a decision to discontinue participation. We also identified an opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 9 publications
3
30
0
6
Order By: Relevance
“…While points and rankings were considered to be key features for enjoyment by Foldit players, they were perceived as creating competition but not fun by GZ participants. This finding is consistent with previous studies which found that the same competitive mechanisms can be rewarding for some and demotivating for others (Eveleigh et al 2013;Bowser et al 2013;Preist et al 2014). For example, previous results found that when leaderboards were used by participants to compare with what others were doing, they were motivating for high-scoring participants, but off-putting for low-scoring participants who felt they could not catch up (Preist et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While points and rankings were considered to be key features for enjoyment by Foldit players, they were perceived as creating competition but not fun by GZ participants. This finding is consistent with previous studies which found that the same competitive mechanisms can be rewarding for some and demotivating for others (Eveleigh et al 2013;Bowser et al 2013;Preist et al 2014). For example, previous results found that when leaderboards were used by participants to compare with what others were doing, they were motivating for high-scoring participants, but off-putting for low-scoring participants who felt they could not catch up (Preist et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In their recent study of the relationship between crowdsourcing, motivation, and engagement in Eyewire, Tinati et al (2017) found that despite the use of gamification in the citizen science task, intrinsic motivations including aiding a beneficial cause, advancing scientific knowledge, and learning were the most highly rated reasons to participate. However, the use of gamification within citizen science has also been shown to be task and domain specific (Eveleigh et al 2013 andTang 2015), and may have negative effects on sustaining engagement. When Tinati et al (2017) used the term despite (emphasis in original) to indicate that intrinsic motivations were the most highly rated reasons to participate, in spite of the use of games, they may refer to the normative desirability of using games in science questioned by some critics, who have warned against the use of the crowdsourcing model of research with its potential to cause harm to participants and manipulate the participant into continued participation (Graber and Graber 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Note that we have presented parts of our interview dataset at workshops and conferences Kloetzer et al, 2013;Eveleigh et al, 2013;Eveleigh et al, 2014]. However this is the first time we have presented our analysis of the full dataset, with the goal of building a model of motivation, learning and creativity.…”
Section: Methodsmentioning
confidence: 99%
“…However, the expectation that gamification is always positive is unrealistic, and it may appeal more to particular groups, such as millennials (Bowser et al 2013). The effect of gamification on volunteer engagement is challenging to generalize when participants react both positively and negatively (Eveleigh et al 2013, Massung et al 2013. Thus, while gamification is probably 1 in a set of components designed to attract and sustain participation, further research is required (Greenhill et al 2014).…”
Section: Participant Contributionsmentioning
confidence: 99%